First-Year Principals in Urban School Districts How Actions and Working Conditions Relate to Outcomes - Burkhauser, Susan (RAND Corporation, 2012)
Principals new to their school face a variety of challenges that can influence their likelihood of improving their schools' performance and their likelihood of remaining the principal. The authors present research on first-year principals' experiences, actions, working conditions, and outcomes. The research is intended to inform efforts to promote school improvement and principal retention.